Extraction of molybdenum from spent NiMo hydrocracking catalysts assisted by ionizing radiation. (February 2022) - Kondo, F.M.; Duarte, C.L.; Somessari, S.L.; Sato, M.I.; Salvador, V.L.R.; Lima, N.B.; Martinelli, J.R.; Calvo, W.A.P.
Abstract: A catalyst is a substance that changes the rate of a reaction. In the petroleum industry, the catalysts are commonly used for fluid catalytic cracking and hydrocracking carried out with catalyst, each of them applied in a specific stage. These catalysts are used to facilitate the molecular chains cracking, which will generate a mixture of hydrocarbons. However, the catalyst gradually loses its activity, either by changing its original molecular structure or by its contamination from other petroleum molecules. The application of ionizing radiation (medium-energy electron beam) over these spent catalysts was studied to contribute the extraction of metals or rare-earths of high added-value. Tests conducted with hydrocracking catalysts were used the technique of electron beam irradiation (1.3 MeV) and had as a subject the extraction of molybdenum. Energy Dispersive X-ray analysis was performed on a Shimadzu EDX-720/800HS and X-ray Diffraction analysis on a Rigaku MultiFlex. Electron beam irradiation had a positive contribution if compared to traditional thermal and chemical methods. In temperature around 750 °C, hydrocracking irradiated catalysts of the lower region have an extraction of molybdenum (MoO3 ) yield twice higher compared to non-irradiated ones, in other words 57.65% and 26.24%, respectively. Highlights: EBA (1.5 MeV) application on the hazardous waste hydrocracking catalysts was studied. EB can decompose supported Ni(Co)–Mo/Al2 O3 sulfide catalyst and organic fragments. EB recoveries Co and remove catalyst impregnated with coke of crude oil distillation. Irradiation (25.3 kGy/s) of HCC spent catalyst had benefits compared to thermal method. HCC irradiated catalysts have an extraction of Mo(MoO3 ) yield twice higher at 750 °C.